Microglia change from a reactive to an age-like phenotype with the time in culture - Caldeira, Cláudia; Oliveira, Ana F.; Cunha, Carolina; Vaz, Ana R.; Falcão, Ana S.; Fernandes, Adelaide; Brites, Dora (Frontiers in Cellular Neuroscience, 2014)
Age-related neurodegenerative diseases have been associated with chronic neuroinflammation and microglia activation. However, cumulative evidence supports that inflammation only occurs at an early stage once microglia change the endogenous characteristics with ageing and switch to irresponsive/senescent and dystrophic phenotypes with disease progression. Thus, it will be important to have the means to assess the role of reactive and aged microglia when studying advanced brain neurodegeneration processes and age-associated related disorders. Yet, most studies are done with microglia from neonates since there are no adequate means to isolate degenerating microglia for experimentation. Indeed, only a few studies report microglia isolation from aged animals, using either short-term cultures or high concentrations of mitogens in the medium, which trigger microglia reactivity. The purpose of this study was to develop an experimental process to naturally age microglia after isolation from neonatal mice and to characterize the cultured cells at 2 days in vitro (DIV), 10 DIV and 16 DIV. We found that 2 DIV (young) microglia had predominant amoeboid morphology and markers of stressed/reactive phenotype. In contrast, 16 DIV (aged) microglia evidenced ramified morphology and increased metalloproteinase (MMP)-2 activation, as well as reduced MMP-9, glutamate release and nuclear factor kappa-B activation, in parallel with decreased expression of Toll-like receptor (TLR)-2 and TLR-4, capacity to migrate and phagocytose. These findings together with the reduced expression of microRNA (miR)-124, and miR-155, decreased autophagy, enhanced senescence associated beta-galactosidase activity and elevated miR-146a expression, are suggestive that 16 DIV cells mainly correspond to irresponsive/senescent microglia. Data indicate that the model represent an opportunity to understand and control microglial aging, as well as to explore strategies to recover microglia surveillance function.